(untitled) (Revista Latino-Americana de Enfermagem, 2002)
In the last few decades, group psychotherapy has deserved considerable attention from researchers. Based on recent publications, the authors of this work make considerations concerning the indication, the need to adopt a selection criteria, expected results and prognoses as well as the change process. Literature review shows a tendency to recognize the client as an agent for his own change. The particular shape which is taken by this process in group psychotherapy is pointed out.